SIMPLIFIED SUPPLIER SELECTION CRITERIA IN SMALL AND MEDIUM ENTERPRISES: A FUZZY AHP APPROACH - Harwati; Widodo, Imam Djati; Cahyo, Winda Nur (JEMIS (Journal of Engineering & Management in Industrial System), 2025)
Many SMEs struggle when it comes to supplier selection due to the large number of criteria available. Because SMEs lack sufficient human resources and sufficient time, they cannot use complex supplier selection criteria and calculations. This research aims to create an efficient and straightforward supplier selection model. At the commencement, a literature review of 46 articles (2021-2022) generates 15 key suppliers selection criteria. The 80/20 Pareto principles state that delivery, price, quality, and service are the four main criteria. The Fuzzy Analytical Hierarchy Process is used to calculate the weighting of each criterion. According to the preferences of ten experts, the weights for price, delivery, quality, and service are 40%, 30%, 25% and 5% respectively. Ten supplier selection cases from literature are used to validate the process. This means that a simple model using the Fuzzy AHP approach will produce supplier rankings of identical supplier types which is 80% similar to the complex model of multi-criteria. This study contributes theoretically to the MCDM literature through a demonstration that reduced-criteria models can retain decision quality while increasing applicability. The model enables SMEs to easily make a reliable supplier selection choice.